Age and Reason of First Dental Visit among 0-14 years Old Children visiting Tertiary Care Center in Koshi Province - Bhagat, Tarakant; Shrestha, Ashish; Kumari Agrawal, Santosh; Dali, Mamta; Ojha, Ashma (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Introduction: The first dental visit should occur within 1 year of child’s age. Majority of parents bring their children for first dental visit only when there is a dental problem.Objective: This study was conducted to determine age and reason of first dental visit and to assess parents’ knowledge and attitude towards the first dental visit of the child.Methods: A cross sectional questionnaire-based study was conducted among 425 parents of children aged 0-14 years visiting the dental outpatient department. Each parent was interviewed by a single examiner. Descriptive statistics and Chi square test were used to report the data. The level of significance was set at p